EUV emission spectra from excited Ar, Xe and Sn ions produced in capillary discharges - Nowakowska-Langier, K.; Jakubowski, L.; Baronova, E.O.; Czaus, K.; Rabinski, M.; Mirowski, R.; Jakubowski, M.J.; Wiraszka, A. (Вопросы атомной науки и техники, 2008)
This work presents preliminary results of an extreme ultraviolet emission obserwations of a capillary discharge plasma. The main purpose of measurements was to demonstrate the spectral range covered by the system working parameters. The spectroscopic studies were carried out by means of an XEUV spectrometer in the Johann geometry. The results provide general information about the radiation processes from the xenon, argon and tin plasma in the range from 12 to 63 nm.